Evaluation of Biochemical Parameters for Sickle Cell Anemic Children at Kassala City, Eastern Sudan - Eltayeb, Ali Hamed; Alshaikh, Menass Isam; Ali, Abdalla Eltoum; Modawe, GadAllah (مجلة الجزيرة للعلوم الصحية; مجلد 2 عدد 16 (2020), 2021)
Background: Sickle cell disease (SCD) is an inherited disease caused by gene mutation. Many investigators reported that Eastern Sudan has rich SCD and also an association with biochemical parameters such as liver and renal function tests. Objective: The present study was to assess the plasma biochemical parameters such as urea, creatinine and sodium (Na) and potassium (K) total protein, albumin, Bilirubin, Aspartate Transaminase (AST), Alanine Transaminase (ALT) and Alkaline Phosphatase (ALP) in SCD as case group and apparently healthy persons as control group. Materials and Methods: The study was conducted at Kassala Teaching Hospital, Kassala city, Eastern Sudan. This study was carried during December 2019 to January 2020. A total of 100 subjects enrolled in this study, 50 patients with SCD as case group and 50 apparently healthy as control group. The plasma biochemical parameters were estimated using Biosystem-350(Semi automated chemistry analyzer), and plasma Na and K were estimated using Easylyte. The data was analyzed using SPSS version (23). Results: Study populations were matched age and sex, the age ranged from 5 to 15 years with their average age 8years. The plasma Na was insignificance difference in case compared to control group. The plasma K, urea and creatinine (p=0.039) were significantly increase compared to control group. Also the plasma total protein, albumin, Bilirubin, creatinine, AST, ALT and ALP were significantly increase in case group compared to control group. The age was strong association into plasma urea(r=0.583, p=.000) and plasma crearinine (r=0.759, p=.000). The negative correlation between plasma Na and plasma urea (r= -.335, p=0.017). There was positive correlation between plasma urea and creatinine (r=0.332, p=0.018).  Their strong association between plasma Bilirubin and ALP activity (r= .563, P=.000), and also their strongly association between liver enzymes plasma level among SCD patients (r=.873, 381, 563, P= .000, .006, 000). Conclusion: The study concluded that, significance increased in plasma K, urea creatinine, plasma total protein, and albumin, Bilirubin, AST, ALT and ALP. Strong association between age and    plasma urea, creatinine, and the negative correlation between plasma Na and plasma urea and also positive correlation between plasma urea and creatinine. There were positive correlation between plasma urea and creatinine.  Their strong association between plasma bilirubin and ALP levels and also their strongly association between liver enzymes levels among SCD patients. Observation of the study concludes the biochemical abnormality play a significant role in sickle cell patient’s physiopathology and can be used to management of the disease.